Corporate Governance: A Focus on Disclosure and Transparency Practices of National Mineral Development Corporation Ltd.(NDMC) - Akber Ali Khan, Mohd.; Fatima, Faresa (Indian Journal of Finance, 2009)
Disclosure and Transparency is generally perceived to have a cardinal role in corporate governance. Indeed, increased disclosure requirements are a response to the corporate governance failures of large US firms such as Enron Corporation and Worldcom.This study attempts to investigate disclosure by public sector entreprise listed in six major stock exchanges in India and explores that increased disclosure is perceived as better governance because disclosure enables better decision making by actors in the capital markets.The research method adopted in this paper is to compute disclosure score of National Mineral Development Corporation Ltd by using guidelines issued by the Department of Public Enterprises and data from the firm’s annual reports. Appropriate statistical tools have been used for finding the impact of disclosures on market valuation of the firm. The results of the study reveal that increase in disclosure and transparency is associated to improved performance.